Distribution of Potential Resources, Reserves and Use of Coal in Indonesia - Fitrya Monica; Marisa Meliana Fitri; Iswandi Umar; Ali Amran; Mulya Gusman (Science and Environmental Journal for Postgraduate, 2023)
Indonesia has abundant coal resources and is a well-known mining sector as a producer and exporter of coal. Even though Indonesia has adequate coal reserves, the ever-increasing energy needs pose challenges in meeting domestic and export needs. Therefore, this study aims to analyze the potential of coal resources and reserves in Indonesia, their utilization in the electricity sector, and find solutions for sustainable use of non-renewable energy. This research uses the method of literature study or literature search. The data sources used are accredited academic journals and related publications, as well as secondary data from the Geological Agency of the Ministry of Energy and Mineral Resources [ESDM] and Recapitulation of Coal Reserve Balance in Indonesia. The results of this study classify coal resources and reserves based on SNI 5015 - 2019 classification. There are several categories, such as inferred coal resources, indicated coal resources, measured coal resources, probable coal reserves, and proven coal reserves. Geologically, economically valuable coal deposits are found in Sumatra and Kalimantan. Coal quality can be classified based on calorific value, such as low, medium, high, and very high calories. With a better understanding of available coal resources, it is hoped that sustainable solutions for future energy needs will be developed.